Aspergillus spp. and azole-resistance characterization on Filtering Respiratory Protective Devices from waste sorting industry - Viegas, Carla (2021)
Studies performed on waste management industry have reported Aspergillus as the most frequent genera on waste-sorting, incineration and composting. Filtering Respiratory Protective Devices (FRPD) are disposable after one-day use (workshift) and their use is mandatory in Portuguese waste-sorting industries. During FRPD use, humidity and temperature conditions provide a favorable environment for the growth of retained Aspergillus. The aim of this study was to characterize Aspergillus spp. presence in FRPD interior layer and exhalation valves, as well as to detect possible azole-resistant isolates in this complex indoor environment. Methods The analyzed samples consisted of 120 FRPD (interior layer and exhalation valves). Fungal load was extracted from both matrixes with 10 mL of 0.1% Tween™ 80 saline solution (NaCl 0.9%) for 30 min at 250 rpm, and 150 μL of those extracts were streaked onto malt extract agar (MEA) supplemented with chloramphenicol (0.05%) and dichloran glycerol agar (DG18). After incubation at 27 ºC for 5 to 7 days Aspergillus spp. densities (CFU/m2) were calculated, and Aspergillus sections were identified through macro and microscopic characteristics. The frequency of azole-resistance was determined by inoculation of the extracts onto screening agar plates containing Sabouraud dextrose agar media supplemented with 4 mg/L itraconazole (ITRA), 1 mg/L voriconazole (VORI), and 0.5 mg/L posaconazole (POSA), incubated at 27 °C for 5 days. Results Aspergillus spp. was detected in both interior layers (77 out of 120; 64.17%) and exhalation valves (63 out of 120; 52.5%). Among the Aspergillus genera, section Fumigati presented the highest frequency, both in exhalation valves (76.57% MEA; 87.24% DG18) and in interior layers (75.81% MEA; 51.22% DG18). Fumigati and Nigri were the Aspergillus sections isolated more frequently on MEA. In addition, Flavi, Circumdati and Candidi sections were also frequently isolated on DG18. Restricti and Aspergilli sections were observed occasionally. DG18 allowed the detection of a more diversified set of Aspergillus species than MEA (in both FRPD matrixes). In azole-supplemented media, Aspergillus spp. was the most frequently found genus on exhalation valves (75.0% of the isolates that grew onto ITRA), suggesting that resistant isolates to ITRA at the tested concentration might be present in this occupational environment. Conclusions This study reports contamination of FRPD used by workers at waste industry with Aspergillus and Aspergillus isolates exhibiting reduced susceptibility to azoles. Future trials should be performed to test the protective efficacy of FRPD and to establish deadlines for FRPD replacement. Monitoring of the establishment of azole-resistant strains in this work environment should be continued to reduce the risk of exposure and consequent development of fungal infections.